Mudanças espaço-temporais no uso e cobertura do solo no parque nacional da Furna Feia/RN - Leite, Paulo Henrique da Silva (Universidade Federal Rural do Semi-Árido, 2019)
The Caatinga is one of the semi-populated and populated regions of the world, mostly a poor and explicit population in a non-sustainable way in the environment in which they live. In this context, as conservation units of an important tool for the conservation of biodiversity and landscape plots, we contribute to human well-being and environmental protection. Thus, the present study aimed to assess and quantify the spatial and temporal changes in land use and land cover in the area that today comprises the Furna National Park and adjacent areas over the past 29 years. (2000), 1999, 2008 (Landsat 5) and 2018 (Landsat 8). With the aid of free software, QGIS 2.18.26, through the SCP plug-in, was created through the application of colored lights, the classification of luminosity and the calculation of the accuracy of each classification. With the r.report algorithm and the LecoS complement, a coverage area and an introduction for each class were calculated respectively. Two incursions were made in the study area to capture coordinates and photographic record of the landscape units for data validation. With a false-dye composition it was possible to distinguish five units of the landscape, which are: a type of new type, a new type of vegetation, a type III, a soil without cover and water bodies. In the National Park, with emphasis on the type I nature coverage area (19.9%), recent urbanization area III (11.7%), scenario type II (6.4%) and ground without coverage (1 , 8%). In the buffer zone, news-growth of areas of type I (7.5%) and new type II (5.5%) areas, and rise in areas of type III vegetation (11.7%) and of soil without cover (1.2%). In both zones, the contribution of water bodies was very low (less than 0.5%). The most recent negative changes occurred between 1989 and 1999, with an increase in the area of soil without cover. Between 1999 and 2008, all units in the zone are changed in the domains of both zones. Oriented blades more rapidly occurred between 2008 and 2018, with an increase in the growth area and the area of soil without cover. Most of the positive changes took place between 2008 and 2018, being more accentuated within the National Park area, a time interval that includes a creation of the National Park. Results demonstrated a significant importance of the Conservation Units, since they are positive, such as the increase of the type I nature, which can be interpreted as regeneration of the Caatinga and the reduction of the type III nature and without coverage, especially in the conservation unit. Most of the negative changes from the environmental point of view began between 1989 and 1999, a period characterized by large-scale irrigated fruit growing, presenting itself as the largest areas of land without cover and type II vegetation. In view of this, it is possible to infer that the main modifying agent of the landscape was an anthropic action associated with the scientific production of fruit and the creation of a conservation unit of a fundamental part for the regeneration of vegetation.
Monografia
Keywords: Uso e ocupação de unidade de conservação; Cobertura do solo; Zona de amortecimento; Sensoriamento remoto; Paisagem; Conservation unit use and occupation; Ground cover; Damping zone; Remote sensing; Landscape; CIENCIAS BIOLOGICAS::ECOLOGIA